Ancilla-Mediated Higher Entanglement as T-Duality, a Categorial Conjecture - Andrei T. Patrascu (Quantum Reports)
In this article, I start with a general presentation of the ideas behind sigma models and higher gauge theories and introduce the possibility of a higher entanglement structure. Using a higher categorial interpretation of entanglement involving gauge theories and <semantics>σ</semantics>-models instead of qubits, one recovers T-duality as a form of ancilla aided entanglement generation. This opens the way towards new dualities in gauge theories and <semantics>σ</semantics>-models produced by means of analogies with quantum circuits of various types.